Cicero und Andokides - Pierzak, Damian (Collectanea Philologica, 2023)
Due to the fact that Andocides is nowhere mentioned in Cicero’s oeuvre it is universally assumed that Cicero could not have read, let alone been inspired by, the works of Andocides. By comparing several passages from both orators, this paper argues that this is not necessarily the case. In terms of both language and content, these texts bear so close a resemblance to one another, that a direct inﬂuence does not seem beyond question. If Cicero had indeed, whether deliberately or otherwise, borrowed some ideas and/or phrases from Andocides, the absence of the latter’s name in Cicero’s extant writings can be explained in two diﬀerent ways: (1) either certain expressions that occur in Andocides’ speeches could have been known to Cicero from indirect tradition, (2) or Cicero was simply reluctant to admit to his acquaintance with the least esteemed of the ten Attic orators.